2019
DOI: 10.1111/1758-5899.12680
|View full text |Cite
|
Sign up to set email alerts
|

Taking Complex Systems Seriously: Visualizing and Modeling the Dynamics of Sustainable Peace

Abstract: The recent United Nation Secretary General's report on sustaining peace speaks to an urgent crisis of complexity in global affairs, where a wide assortment of nonstate actors wields more political power than ever before. In this context, the international community's traditional ways of forecasting, planning, policymaking, and assessing impact are becoming rapidly obsolete. In response, policymakers are calling for more holistic or systemic approaches to peace and development. Unfortunately, these proposed cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous calls for improving effective environmental action have noted the importance of institutional change at the global level (Biermann et al 2012). Similarly, in this paper we propose to investigate the processes, structures, and institutions that enable us to effectively manage the dilemmas inherent to the sustainability agenda (Fisher and Coleman 2019). We understand the SDGs themselves as insufficient decision-support instruments, and a deeper study of the complex system and multiple forces that lead to the goals themselves is necessary (Allen et al 2020).…”
Section: The Need For a Model Of Integrated Sustainabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous calls for improving effective environmental action have noted the importance of institutional change at the global level (Biermann et al 2012). Similarly, in this paper we propose to investigate the processes, structures, and institutions that enable us to effectively manage the dilemmas inherent to the sustainability agenda (Fisher and Coleman 2019). We understand the SDGs themselves as insufficient decision-support instruments, and a deeper study of the complex system and multiple forces that lead to the goals themselves is necessary (Allen et al 2020).…”
Section: The Need For a Model Of Integrated Sustainabilitymentioning
confidence: 98%
“…Both formal and informal institutions are utilized by societies to manage conflicts, but with regards to this proposition we assert that institutions that both enable cooperation across networks and social ties as well as those that effectively regulate competition are required to pursue the sustainability agenda (Schnegg 2018 ). This proposition draws on a well-established body of research related to effective cooperation and conflict resolution (Coleman et al 2017a , 2019 ; b ; Deutsch 1973 , 1985 , 2006 ; Rubin et al 1994 ).…”
Section: The Need For a Model Of Integrated Sustainabilitymentioning
confidence: 99%
“…Below, the procedures and preliminary findings from the six project components are outlined in brief (for more complete descriptions, see Coleman et al, 2019, 2020; Liebovitch et al, 2019; Mazzaro et al, 2015).…”
Section: The Spp: Its Origins and Structurementioning
confidence: 99%
“…What was learned from the causal loop diagram proposed by Coleman et al (2017)? (1) We identified 25 “peace factors” that are important in generating and sustaining peace.…”
Section: Understanding Systemsmentioning
confidence: 99%